"Mr. Enthusiasm" : Bill Zorn, Athletic Director, Dean of Men, Coach, Instructor University of Wisconsin-Eau Claire, 1928-1968 - Ryan, Zachary J. (My University, 2009)
Willis "Bill" Zorn was an administrator, athletic director, coach, and instructor at the University of Wisconsin-Eau Claire for over 40 years in the twentieth century. He was a very prominent figure at the university during his tenure and is still recognized today at UW-Eau Claire in the hallways at W.L. Zorn Arena. The arena dedicated to Zorn is home of the UW-Eau Claire Men's and Women's basketball teams, as well as the commencement ceremonies and other events at the university. His role at the school was instrumental in the development of intercollegiate athletics. This paper will go in depth into Zorn's policies as coach and administrator, and how they changed the university. In addition, the paper will analyze Zorn's roles on campus and perceptions of him from students, athletes, and faculty. I will also give a brief history on the development of intercollegiate athletics to put Zorn's work at Eau Claire into historical context.
Keywords: Zorn, Bill; University of Wisconsin--Eau Claire--Sports--History; College sports--Wisconsin--Eau Claire--History; College administrators--Wisconsin--Eau Claire--Biography; Coaches (Athletics)--Wisconsin--Eau Claire--Biography